Public Health Information and Misinformation through Digital Technology in Uganda: Legal Responsibility of the State - Paul Atagamen Aidonojie; Esther Chetachukwu Aidonojie; Mercy Okpoko; Micheal Inagbor; Obieshi Eregbuonye (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
In recent years, the advent of social media, mobile communication, and online news platforms has greatly changed the way public health information is produced, spread, and consumed. Besides this, the rise in Internet usage for health-related information has also made the public more susceptible to false or deceptive information, thereby giving rise to numerous problems, such as public health, trust in institutions, and the effectiveness of controlling diseases. The Ugandan government must implement digital solutions to combat public health misinformation because this task safeguards citizens' health rights and their right to receive accurate information, which helps maintain public safety. Consequently, the purpose of the study is to evaluate the state’s legal obligations to the extent that it can prevent, correct, and respond to misinformation on public health issues, as well as to examine the current legislative and regulatory framework governing digital governance and public health in light of this. Using a doctrinal research method based on the PRISMA framework, the study comprehensively studies both primary and secondary legal sources. The outcome indicates that, given the sophisticated nature of digital technology, the existing regulations are mainly reactive, dealing with punishment more often than prevention or correction of the misinformation. The study ends with the suggestion that the mechanism of regulatory enforcement should change from one that is mostly punitive to one that is preventive and corrective in nature. Among other things, it will mean requiring an active public health messaging, having real-time fact-checking systems, and having the official digital channels work together to correct misinformation.